Herbert Marcuse as Social Justice Educator : A Critical Introduction - Reitz, Charles (Critical interventions (Boulder, Colo.), 2025)
Demonstrating the continued relevance of Marcuse's work, Herbert Marcuse as Social Justice Educator details how his work remains a countervailing force to the conventional wisdom in intellectual and political matters today.